PELATIHAN PENGGUNAAN ALAT PERAGA SAINS BAGI SISWA SMP NATHANIA PALANGKA RAYA - Kadek Ayu Cintya Adelia; Ety Kurniati; Indah Gumilang Dwinanda (LPPM Universitas Bina Bangsa, 2024)
Mastery of science and technology is important in building competitiveness in order to produce value-added products and provide competitive advantages. Mastery of science and technology can be improved through various sciences, one of which is natural science (IPA). Natural science is a collection of knowledge and processes carried out by scientists in conducting investigations to obtain explanations about natural phenomena that occur in everyday life. One step in having the strategy in question is mastering the techniques for presenting material or what is usually called teaching methods. The use of practical teaching aids helps make it easier for teachers to explain a concept to students. Nathania Palangka Raya Middle School is located in the center of Palangka Raya city, Central Kalimantan Province. Based on the survey results, science learning carried out by teachers still uses conventional methods and without the help of learning media. Apart from that, teachers still dominate the science learning process. One way to improve the abilities of teachers and students in the field of science requires training and use of science teaching aids. The result of this training is that students are enthusiastic about participating in activities organized by the service team. In addition, students' understanding of the material taught using science teaching aids is better than without using science teaching aids and also increasing teacher abilities, will contribute to the improvement students' understanding of science concepts